2022
DOI: 10.1002/slct.202201682
|View full text |Cite
|
Sign up to set email alerts
|

Greenly Reduced CoFe‐PBA/Nickel Foam: A Robust Dual Electrocatalyst for Solar‐Driven Alkaline Water Electrolysis with a Low Cell Voltage

Abstract: Development of eco-friendly efficient dual electrocatalyst for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) gaining increased attention for renewable energy production. Here, the greenly synthesized rCoFe-PBA was established as durable and effective bifunctional electrocatalyst for HER and OER process. The rCoFe-PBA coated Nickel foam electrode exhibit overpotential of 311 mV (OER) and 100 mV (HER) @ 10 mA cm À 2 significantly lower than commercial IrO 2 (381 mV) and near to Pt/C (36 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 128 publications
1
28
0
Order By: Relevance
“…It can also provide a perfect pathway for evolution of O 2 and H 2 gas from the electrode surface without causing damage. 42,43 The most significant pore volumes of Fe-PANI electrocatalyst indicated that it is mainly macroporous, which is quite consistent with the effective OER and HER activity.…”
Section: Njc Papersupporting
confidence: 53%
See 3 more Smart Citations
“…It can also provide a perfect pathway for evolution of O 2 and H 2 gas from the electrode surface without causing damage. 42,43 The most significant pore volumes of Fe-PANI electrocatalyst indicated that it is mainly macroporous, which is quite consistent with the effective OER and HER activity.…”
Section: Njc Papersupporting
confidence: 53%
“…22). 43,60 The LSV curves indicate that the efficiency of Fe-PANI/NF// Fe-PANI/NF was superior to that of NF//NF (Fig. 22).…”
Section: Njc Papermentioning
confidence: 98%
See 2 more Smart Citations
“…The electrochemical water splitting into H 2 and O 2 has been trusted as one of the propitious approaches to obtain spotless fuel from renewable energy sources . However, the huge process of electrochemical water splitting was mostly impeded by the slow anodic reaction [oxygen evolution reaction (OER)], where O–H bond dissociation with subsequent O–O bond making has been involved. , A suitable OER catalyst can address these difficulties by combining numerous proton and electron transfer for oxygen evolution at a low overpotential (η). Most widely used ruthenium oxide (RuO 2 ) and iridium oxide (IrO 2 ) are the best OER catalysts; nevertheless, they are scarce and expensive. , Hence, alternative OER catalysts from 3d transition metals (Fe, Co, Ni, and Mn), mixed metal oxides (hydroxides), perovskites, phosphates, borides, chalcogenides, and molecular catalysts have been investigated. , However, still significant development is required to reduce the price of the catalyst with improved OER activity and stability. Bimetal oxides/hydroxides are one of the materials for high-performance electrodes along with several oxidation states because of the synergistic interaction between both metals with multivalent transitions in the quick Faraday reactions. , In the midst of various bimetal oxides/hydroxides, Co–Ni hydroxide has attracted attention as a result of the higher efficiency, good theoretical capacitance, and cooperative effect of Co and Ni .…”
Section: Introductionmentioning
confidence: 99%